A review of successes, challenges, and lessons from Indigenous protected and conserved areas. (January 2020) - Tran, Tanya C.; Ban, Natalie C.; Bhattacharyya, Jonaki
Highlights: Indigenous Peoples created IPCAs independently and through various partnerships. Indigenous resurgence and resiliency, and valuing conservation influenced IPCAs. IPCAs had tangible socio-cultural, political, and ecological benefits. Challenges limited benefits and strained governance and management capacities. Work to improve state conservation frameworks is needed to better support IPCAs. Abstract: Indigenous Peoples' protected and conserved areas have gained global attention due to growing interest in protecting biodiversity during a time of Indigenous resurgence. We reviewed the academic literature to synthesize the motivations, successes, challenges, and lessons from protected and conserved areas led by Indigenous Peoples globally. We found and analyzed 58 papers, describing 86 specific initiatives involving at least 68 Indigenous Peoples across 25 countries. We found that Indigenous Peoples established protected and conserved areas independently and through local- and broad-scale partnerships. States that supported such efforts did so through formal legislation, agreements, and policies, and informally through local relationships and shared values. Indigenous Peoples' protected and conserved areas created socio-cultural, political, and ecological benefits such as improving Indigenous livelihoods, increasing governance and management capacities, and improving species populations and habitat protection. However, some challenges (e.g. restrictive legislations, burdensome partnerships, insufficient funding) limited benefits, and demanded additional capacities and resources for mitigation. We recommend that states and other external actors: create and improve policies, legislations, and resources for Indigenous Peoples' protected and conserved areas as defined by Indigenous Peoples; provide resources and facilitate Indigenous leadership to shape external mechanisms for protected area establishment and development; and create new internal mechanisms for Indigenous engagement and partnerships. Indigenous Peoples would benefit from building partnerships to support and manage their areas. Finally, we suggest that managers commit more resources to effectively monitor and manage these areas, including integrating management priorities with local and larger scale socio-cultural and environmental issues that affect these areas.